High expression level of SOX2 is significantly associated with shorter survival in patients with thymic epithelial tumors. (June 2019) - Lee, Guk Jin; Lee, Heejung; Woo, In Sook; Kim, Taejung; An, Ho Jung; Choi, Hyun Joo; Lee, Youn Soo; Lee, Kyo Young; Lee, Jieun; Kang, Jin-Hyoung
Highlights: Thymic epithelial tumors (TET) are divided into two broad categories, thymoma (TM) and thymic carcinoma (TC). Molecular biology of TETs are poorly understood. We suggest that SOX2 might be potential biomarker to predict biologic aggressiveness and poor prognosis in TETs. Abstract: Objectives: Thymic epithelial tumors (TET) are heterogenous tumors which are composed of thymoma (TM) and thymic carcinoma (TC). We attempted to determine differences in gene expression between TM and TC, and to determine the effect of such genes on the prognosis of patients with TET. Materials and methods: Gene expression profiles of SOX2, OCT-4, IGF-1, IGF-1R and IR mRNA transcripts in tumor tissues of TM and TC were determined using real-time PCR (RT-PCR). We constructed tissue microarray with 140 paraffin-embedded tumor tissues and performed immunohistochemistry (IHC) for IGF-1R-related signaling molecules, including SOX2, IGF-1, IGF-1R and pAKT. Results: SOX2 mRNA expression was notably higher (216-fold) in TCs than in TMs. However, there was no significant difference in expression of IGF-1, IGF-1R, OCT-4 or IR between the two tumor types. In IHC results, SOX2 (HR: 7.57, P = 0.001) and IGF-1 (HR: 9.43, P = 0.001) expression levels in TC were significantly higher than those in TM. There was a significant correlation in expression of SOX2 with IGF-1 (P = 0.021) and pAKT (P = 0.026). In univariate analysis, clinical TNM stage, WHO classification, serum LDH, expression of SOX2, IGF-1R, IGF-1 and pAKT, were significantly correlated with overall survival (OS). Multivariate analysis using a forward-selection procedure revealed that clinical N stage (HR: 4.08, P < 0.001), M stage (HR: 3.37, P = 0.001) and SOX2 expression (HR: 4.53, P = 0.010) were significantly associated with OS. Conclusions: SOX2 is expressed significantly higher in TC than in TM. SOX2 expression is also closely related to IGF-1 and pAKT expression. The higher expression of SOX2 is significantly associated with shorter survival in patients with TET.